Disease and Injury Epidemiology Among Military Personnel Deployed to West Africa During the 2014–2015 Ebola Outbreak - Markelz, Ana (Open Forum Infect Dis, 2017)
BACKGROUND: In November 2014, in response to the Ebola outbreak, the US government sent ~3000 military personnel to West Africa to construct Ebola treatment units, train health care workers and enhance laboratory testing capabilities. We describe the observed disease and injury epidemiology to identify trends, optimize preventive measures, and mitigate illness during future military operations. METHODS: Disease and injury visits were monitored daily from December 1, 2014 to February 25, 2015 and categorized by illness and injury type. The personnel were deployed to eight locations in Liberia and Senegal. Diagnostic testing was limited to routine laboratory testing, rapid malaria tests, Ebola PCR, but no rapid tests for other pathogens. Surveillance data were analyzed for disease trend associations (Mann–Whitney U-test, SPSS software). RESULTS: The number of people deployed ranged from 1057 to 2983. There were 2,493 visits (>50% in the first month), with a decline in number of patients, illnesses, injuries, and rates of disease and injury during the surveillance period (P < 0.001). Upper respiratory, gastrointestinal (GI) and dermatologic complaints accounted for the largest number of non-injury visits (373, 325, and 306, respectively) and declined over time (P < 0.001). Fifty-one percent and 73% of visits for injuries and GI complaints, respectively, were seen in the first month. Operational stress, musculoskeletal, and soft tissue injuries decreased from the first to third month (P < 0.001). Enterovirus meningitis, norovirus gastroenteritis, and Chikungunya were diagnosed in patients after medical evacuation or redeployment. No cases of malaria were identified in deployed personnel while in West Africa. CONCLUSION: The disease and injury patterns seen in this humanitarian mission are consistent with surveillance data from combat operations in Iraq and Afghanistan, where GI, respiratory and dermatologic complaints accounted for most of the illnesses and rates declined over time. The high prevalence of upper respiratory and GI illness supports a need for rapid diagnostic platforms in the deployed setting to promptly identify threats to individuals and the mission, minimize communicable disease risks and avoid unnecessary medical evacuations. DISCLOSURES: All authors: No reported disclosures.